The continuum of HIV care in South Africa: implications for achieving the second and third UNAIDS 90-90-90 targets. (20th February 2017) - Takuva, Simbarashe; Brown, Alison E.; Pillay, Yogan; Delpech, Valerie; Puren, Adrian J.
Abstract : Background: We characterize engagement with HIV care in South Africa in 2012 to identify areas for improvement towards achieving global 90-90-90 targets. Methods: Over 3.9 million CD4 + cell count and 2.7 million viral load measurements reported in 2012 in the public sector were extracted from the national laboratory electronic database. The number of persons living with HIV (PLHIV), number and proportion in HIV care, on antiretroviral therapy (ART) and with viral suppression (viral load <400 copies/ml) were estimated and stratified by sex and age group. Modified Poisson regression approach was used to examine associations between sex, age group and viral suppression among persons on ART. Results: We estimate that among 6511 000 PLHIV in South Africa in 2012, 3300 000 individuals (50.7%) accessed care and 32.9% received ART. Although viral suppression was 73.7% among the treated population in 2012, the overall percentage of persons with viral suppression among all PLHIV was 23.8%. Linkage to HIV care was lower among men (38.5%) than among women (57.2%). Overall, 47.1% of those aged 0–14 years and 47.0% of those aged 15–49 years were linked to care compared with 56.2% among those aged above 50 years. Conclusion: Around a quarter of all PLHIV have achieved viral suppression in South Africa. Men and younger persons have poorer linkage to HIV care. Expanding HIV testing, strengthening prompt linkage to care and further expansion of ART are needed for South Africa to reach the 90-90-90 target. Focus on these areas will reduce the transmission of new HIV infections and mortality in the general population. Abstract : Supplemental Digital Content is available in the text